An exploratory analysis of bezisterim treatment associated with decreased biological age acceleration, and improved clinical measure and biomarker changes in mild-to-moderate probable Alzheimer's disease - Christopher L. Reading; Jiayan Yan; Marcia A. Testa; Donald C. Simonson; Hira Javaid; Lisa Schmunk; Daniel E. Martin-Herranz; Robert Brooke; Juozas Gordevicius; Jeffrey Zhang; Harvey Yuan; Clarence Ahlem; et al. (Frontiers in Neuroscience)
IntroductionAging is the primary risk factor for sporadic Alzheimer's disease. Chronic low-grade inflammation associated with aging drives cognitive impairment through multiple mechanisms involving oxidative stress, insulin resistance, and dysregulation of metabolic, immunologic, and hematologic systems.MethodsIn a 7-month, randomized, double-blind, placebo-controlled trial (NCT04669028), we investigated the safety and activity of bezisterim, a first-in-class, oral, blood–brain barrier–permeable, anti-inflammatory agent on cognitive, molecular, biochemical, physiological, and biological aging parameters in a subset of 50 mild-to-moderate probable Alzheimer's disease participants. These participants had source-document-verified clinical measures and samples, and they completed the protocol. This study focuses on epigenetic, metabolic, biomarker, and cognitive measures in the exploratory biomarker population that completed the protocol.ResultsBezisterim was associated with non-significant directional improvements in multiple measures of cognitive and functional performance compared to placebo, with correlations to biological age (determined by DNA methylation “clocks”) and to metabolism, inflammation, and dementia biomarkers. In addition, clinical measures correlated with the extent of DNA methylation of certain cytosine-phosphate-guanine (CpG) sites in genes associated with metabolic inflammation and neurodegeneration.DiscussionThe results suggest the possible use of bezisterim to target the multifactorial processes underlying dementia.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04669028, Identifier: NCT04669028.